Redox-sensitive GFP in Arabidopsis thaliana is a quantitative biosensor for the redox potential of the cellular glutathione redox buffer - Meyer, Andreas; Brach, Thorsten; Marty, Laurent; Hell, Rüdiger (The plant journal, 2007)
The cellular glutathione redox buffer is assumed to be part of signal transduction pathways transmitting environmental signals during biotic and abiotic stress, and thus is essential for regulation of metabolism and development. Ratiometric redox-sensitive GFP (roGFP) expressed in Arabidopsis thaliana reversibly responds to redox changes induced by incubation with H2O2 or DTT. Kinetic analysis of these redox changes, combined with detailed characterization of roGFP2 in vitro, shows that roGFP2 expressed in the cytosol senses the redox potential of the cellular glutathione buffer via glutaredoxin (GRX) as a mediator of reversible electron flow between glutathione and roGFP2. The sensitivity of roGFP2 toward the glutathione redox potential was tested in vivo through manipulating the glutathione (GSH) content of wild-type plants, through expression of roGFP2 in the cytosol of low-GSH mutants and the endoplasmic reticulum (ER) of wild-type plants, as well as through wounding as an example for stress-induced redox changes. Provided the GSH concentration is known, roGFP2 facilitates the determination of the degree of oxidation of the GSH solution. Assuming sufficient glutathione reductase activity and non-limiting NADPH supply, the observed almost full reduction of roGFP2 in vivo suggests that a 2.5 mm cytosolic glutathione buffer would contain only 25 nm oxidized glutathione disulfide (GSSG). The high sensitivity of roGFP2 toward GSSG via GRX enables the use of roGFP2 for monitoring stress-induced redox changes in vivo in real time. The results with roGFP2 as an artificial GRX target further suggest that redox-triggered changes of biologic processes might be linked directly to the glutathione redox potential via GRX as the mediator.